Bone Mineral Density in Children and Adolescents with Congenital Adrenal Hyperplasia - Paulo Alonso Garcia Alves Junior; Daniel Luis Gilban Schueftan; Laura Maria Carvalho de Mendonça; Maria Lucia Fleiuss Farias; Izabel Calland Ricarte Beserra (International Journal of Endocrinology)
Chronic glucocorticoid therapy is associated with reduced bone mineral density. In paediatric patients with congenital adrenal hyperplasia, increased levels of androgens could not only counteract this effect, but could also advance bone age, with interference in the evaluation of densitometry. We evaluate bone mineral density in paediatric patients with classic congenital adrenal hyperplasia taking into account chronological and bone ages at the time of the measurement. Patients aged between 5 and 19 years underwent radiography of the hand and wrist followed by total body and lumbar spine densitometry. Chronological and bone ages were used in the scans interpretation. In fourteen patients, mean bone mineral density Z-score of total body to bone age was −0.76 and of lumbar spine to bone age was −0.26, lower than those related to chronological age (+0.03 and +0.62, resp.). Mean Z-score differences were statistically significant (P=0.004 for total body and P=0.003 for lumbar spine). One patient was classified as having low bone mineral density only when assessed by bone age. We conclude that there was a reduction in the bone mineral density Z-score in classic congenital adrenal hyperplasia paediatric patients when bone age was taken into account instead of chronological age.